1995
DOI: 10.1056/nejm199503163321102
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Trial Comparing Fluconazole with Clotrimazole Troches for the Prevention of Fungal Infections in Patients with Advanced Human Immunodeficiency Virus Infection

Abstract: Fluconazole taken prophylactically reduces the frequency of cryptococcosis, esophageal candidiasis, and superficial fungal infections in HIV-infected patients, especially those with 50 or fewer CD4+ lymphocytes per cubic millimeter, but the drug does not reduce overall mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
126
2
2

Year Published

1995
1995
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 302 publications
(135 citation statements)
references
References 17 publications
5
126
2
2
Order By: Relevance
“…One-dimensional proton NMR spectra of VG16KRKP at 25 C was carried out on a Bruker Avance III 500 MHz NMR spectrometer (equipped with smart probe), followed by a series of 1D titrations using C. neoformans cell suspensions (OD 600 ¼ 1.0) in same buffer amounting to a final range of~10 7 cells. For live cell STD experiments, a 1 mM VG16KRKP solution was prepared in 10 mM deuterated phosphate buffer of pH 7.2 to rule out the possibility of peptide resonance suppression by water (33,34).…”
Section: Nmr Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation
“…One-dimensional proton NMR spectra of VG16KRKP at 25 C was carried out on a Bruker Avance III 500 MHz NMR spectrometer (equipped with smart probe), followed by a series of 1D titrations using C. neoformans cell suspensions (OD 600 ¼ 1.0) in same buffer amounting to a final range of~10 7 cells. For live cell STD experiments, a 1 mM VG16KRKP solution was prepared in 10 mM deuterated phosphate buffer of pH 7.2 to rule out the possibility of peptide resonance suppression by water (33,34).…”
Section: Nmr Spectroscopymentioning
confidence: 99%
“…The current therapeutics approaches mainly include the azole group of drugs (amphotericin B, 5-fluorocytosine, and echinocandins, among others). Most of these are limited by their cytotoxic effects on the host, limited efficacy, or development of resistance in the pathogen upon long-term usage (4)(5)(6)(7). In addition, sessile biofilms act as a store house for antibiotic tolerant fungal cells that can lead to persistent systemic infections (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, a large amount of information has been published on the incidence of thrush and associated factors in periods prior to and following the advent of highly active antiretroviral therapy (HAART) using a single episode of thrush per individual as the unit of analysis 10,11,12 . However, the recurrence of this condition is a very common event in clinical practice, as children living with HIV/AIDS often experience numerous episodes throughout their lives.…”
Section: In Clinical Practice Recurrence Of Thrush Is Common In Chilmentioning
confidence: 99%
“…Fungal disease can be prevented; in a randomized controlled trial in the United States, primary preventive therapy with fluconazole was shown to reduce the incidence of cryptococcal disease, esophageal candidiasis, and superficial fungal infections among HIV-infected individuals, particularly those with CD4 counts less than 50 ϫ 10 6 /L. 68 Fluconazole had no significant effect on mortality in this study, perhaps because of lack of statistical power to detect a difference; mortality rates attributable to fungal disease were low, and the study was not designed to address this issue.…”
Section: Preventing Fungal Diseasementioning
confidence: 99%